Analisis financial distress dampak pandemi covid-19 berdasarkan model grover, springate dan zmijewski pada perusahaan tekstil dan garmen - Armenda , Dea; Hertina , Dede (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research has a purpose to compare the calculation in predicting potential bankruptcy using the Grover, Springate and Zmijewski models and the level of accuracy of the three models. This research is included in quantitative research. The population used in this research were 21 sub-sector companies of the textile and garment industry. The sample used in this research were 18 companies chosen with purposive sampling technique and several criteria that must be met. This research use the Kruskal-Wallis Test and produces theres not any differecers in the result of bankruptcy prediction between the Grover, Springate, and Zmijewski models in Textile and Garment Industry Sub-Sector Companies. The results showed that using the Springate model there were 15 companies predicted to has bankcuptcy potential, 5 companies using the Grover model, and 11 companies using the Zmijewski model. Based on the result, the highest level of accuracy of the third model used is in the Grover model with a percentage of 72.22% and the lowest is in the Springate model with a percentage of 16.67%.